Nilai Organoleptik Hedonik Formulasi Serbuk Minuman Tradisional Dengan Penambahan Serbuk Padina Minor - Nuzul Rahmah Taniu; Nikmawatisusanti Yusuf; Shindy Hamidah Manteu (Samakia : Jurnal Ilmu Perikanan, 2025)
Traditional drinks are drinks made from natural ingredients and have a unique taste. Padina minor is a species of brown seaweed that has bioactive compounds and antioxidant activity that are beneficial for the body so that it can be used as an additional ingredient in making traditional drinks so that it can be used as functional food. This study aims to determine the best formula for traditional drinks with the addition of p.minor. The parameters observed include water content, solubility and antioxidants. The results of the research test showed that the water content of the four formulations including the control met the requirements for the Quality Requirements for Traditional Drink Powder According to the Indonesian National Standard 01-4320-1996, which is a maximum of 3.0%. The results of the solubility test showed the highest solubility value at the P4 concentration of 31.36%. And the results of the antioxidant test showed the presence of strong antioxidant ability in the interval of 50-100 mg / L. This product can be categorized as a functional food with the antioxidant content it contains which can improve health.